The transcriptome landscape of 3D-cultured placental trophoblasts reveals activation of TLR2 and TLR3/7 in response to low Trypanosoma cruzi parasite exposure - Silberstein, Erica; Chung, Charles C.; Debrabant, Alain (Frontiers in Microbiology, 2023)
Vertical transmission of Trypanosoma cruzi (T. cruzi) become a globalized health problem accounting for 22% of new cases of Chagas disease (CD). Congenital infection is now considered the main route of CD spread in non-endemic countries where no routine disease testing of pregnant women is implemented. The main mechanisms that lead to fetal infection by T. cruzi remain poorly understood. Mother-to-child transmission may occur when bloodstream trypomastigotes interact with the syncytiotrophoblasts (SYNs) that cover the placenta chorionic villi. These highly specialized cells function as a physical barrier and modulate immune responses against pathogen infections. To model the human placenta environment, we have previously used a three-dimensional (3D) cell culture system of SYNs that exhibits differentiation characteristics comparable to placental trophoblasts. Further, we have shown that 3D-grown SYNs are highly resistant to T. cruzi infection. In this work, we used RNA sequencing and whole transcriptome analysis to explore the immunological signatures that drive SYNs’ infection control. We found that the largest category of differentially expressed genes (DEGs) are associated with inflammation and innate immunity functions. Quantitative RT-PCR evaluation of selected DEGs, together with detection of cytokines and chemokines in SYNs culture supernatants, confirmed the transcriptome data. Several genes implicated in the Toll-like receptors signaling pathways were upregulated in 3D-grown SYNs. In fact, TLR2 blockade and TLR3/7 knockdown stimulated T. cruzi growth, suggesting that these molecules play a significant role in the host cell response to infection. Ingenuity Pathway Analysis of DEGs predicted the activation of canonical pathways such as S100 protein family, pathogen induced cytokine storm, wound healing, HIF1 signaling and phagosome formation after T. cruzi exposure. Our findings indicate that SYNs resist infection by eliciting a constitutive pro-inflammatory response and modulating multiple defense mechanisms that interfere with the parasite’s intracellular life cycle, contributing to parasite killing and infection control.